What is the source of baseflow in agriculturally fragmented catchments? Complex groundwater/surface‐water interactions in three tributary catchments of the Wabash River, Indiana, USA. Issue 22 (26th September 2017) - Frisbee, Marty D.; Meyers, Zachary P.; Stewart‐Maddox, Noah S.; Caffee, Marc W.; Bogeholz, Philine; Hughes, Madison N.
Abstract: Some conceptual models suggest that baseflow in agriculturally fragmented watersheds may contain little, if any, groundwater. This has critical implications for stream quality and ecosystem functioning. Here, we (a) identify the sources and flowpaths contributing to baseflow using 222 Rn and 87 Sr/ 86 Sr and (b) quantify mean apparent ages of groundwater and baseflow using multiple isotopic tracers (CFC, SF6, 36 Cl, and 3 H) in 4 small (0.08 to 0.64 km 2 ) tributary catchments to the Wabash River in Indiana, USA. 222 Rn activities and 87 Sr/ 86 Sr ratios indicate that baseflow in 3 catchments is sourced primarily from groundwater; baseflow in the fourth is dominated by a source similar to agricultural run‐off. CFC‐12 data indicate that springs in 1 catchment are discharging significant proportions of water that recharged between 1974 (42 ± 2 years) and 1961 (55 ± 2 years). Those same springs have 36 Cl/Cl ratios between 1, 381.08 ± 29.37 (×10 −15 ) and 1, 530.64 ± 27.65 (×10 −15 ) indicating that a substantial proportion of the discharge likely recharged between 1975 (41 years) and 1950 (66 years). Groundwater samples collected from streambed mini‐piezometers in a separate catchment have CFC‐12 concentrations indicating that a large proportion of the recharge occurred between 1948 (68 ± 2 years) and 1950 (66 ± 2 years). Repeat sampling conducted in September 2015 after above‐average summer rainfall did not show significant decreases in mean apparent age. The relatively old ages observed in 3 of the catchments can be explained by geological complexities that are likely present in all 4 catchments, but overwhelmed by flow from the shallow phreatic aquifer in the fourth catchment.